Predictors of clinical progression in HIV-1-infected adults initiating combination antiretroviral therapy with advanced disease in the Asia-Pacific region: Results from the TREAT Asia HIV Observational Database - H. Byakwaga (2018)
The majority of HIV-infected patients in developing countries commences combination antiretroviral therapy (cART) with advanced disease. We examined predictors of disease progression in patients initiating cART with CD4 count ≤200 cells/mm3 in the TREAT Asia HIV Observational Database. The main outcome measure was progression to either an AIDS-defining illness or death occurring 6 months after initiation of cART. We used survival analysis methods. A total of 1255 patients contributed 2696 person years of follow-up; 73 were diagnosed with AIDS and 9 died. The rate of progression to the combined end point was 3.0 per 100 person years. The factors significantly associated with a higher risk of disease progression were Indian ethnicity, infection through intravenous drug use, lower CD4 count, and hemoglobin ≤130 g/dL at 6 months. In conclusion, measurements of CD4 count and hemoglobin at month 6 may be useful for early identification of disease progression in resource-limited settings. © The Author(s) 2012.